Predicting Alcohol Pre-Drinking in Australian Undergraduate Students Using an Integrated Theoretical Model - Caudwell, Kim; Hagger, Martin (Wiley-Blackwell, 2015)
Background: The aim of the present study was to examine the social-cognitive and motivational factors associated with pre-drinking based on a model integrating motivational constructs from self-determination theory and belief-based constructs from the theory of planned behaviour. Methods: A prospective correlational design was used. Participants (N = 286; 66.4% female) completed self-report measures of past alcohol consumption, autonomous and controlled forms of motivation from self-determination theory, and attitudes, subjective norms, perceived behavioural control, and behavioural intentions from the theory of planned behaviour at baseline. Participants reported pre-drinking frequency four weeks later. Results: Variance-based structural equation modelling showed that the hypothesised model predicted 54 per cent of the variance in pre-drinking intentions at baseline, and 20 per cent of the variance in pre-drinking behaviour at follow-up. Mediation analyses indicated strong, statistically significant effects of autonomous motivation on intentions to pre-drink, partially mediated by attitudes and subjective norms. Intention and perceived behavioural control significantly predicted pre-drinking frequency. Conclusions: Results provide support for the hypothesised model relationships. Autonomous motivation, attitude, subjective norm, and perceived behavioural control were influential in forming students' intentions to pre-drink. However, consistent with previous findings, the intention-behaviour relationship was relatively weak. Future research should look to non-intentional and volitional processes that may influence pre-drinking in undergraduates.